Thermoelastic Waves in a Transversely Isotropic Plate with Thermal Relaxations - Chand, D. (Engineering Transactions, 1994)
The generalized form of heat conduction equation is used to study the thermoelastic waves in a transversely isotropic, thermally conducting and infinitely extended, stretched elastic plate due to a cylindrical projectile, in the context of the Green and Lindsay theory of thermoelasticity. The Laplace transform technique is employed to obtain small time solutions. The discontinuities in stresses and temperature have also been discussed at their wavefronts. The jumps obtained have been computed numerically and are illustrated graphically for a single crystal of zinc.